No to a bulging stomach: attitudes and perceptions of education stakeholders on the enrolment of pregnant and mothering students in mainstream high schools in Gweru district - Sifelani, Innocent (Midlands State University, 2018)
This research effort was conducted on the backdrop of unprecedented worldwide record of teenage pregnancy and Zimbabwe has the highest teenage pregnancy rate in Sub-Saharan Africa. Despite numerous legal frameworks and policies, high school dropout cases as a result of pregnancy continue to be recorded. To further compound their demise, pregnant and mothering students suffer stigma and discrimination perpetuated by education stakeholders. The researcher‟s motivation and rationale to undertake this study was based on the need to explore perceptions and attitudes of education stakeholders on the enrollment of pregnant and mothering students in mainstream High schools in Gweru District. For an in-depth understanding of the topic under investigation, the study assumed a qualitative approach guided by interpretivist research paradigm. The study utilized Interpretive Phenomenological Analysis research design which enhanced an appreciation of the participants‟ lived experiences, perceptions and attitudes on the phenomenon under study. Information rich participants were selected through use of purposive sampling technique and the study‟s participants were eight students, two parents and two teachers. Following data collection process through use of the interview technique, data was analyzed using Interpretative Phenomenological Analysis method. The study‟s main revelation is that education stakeholders exhibited mixed reactions on the practice of taking on board pregnant and mothering students in mainstream High schools. It was concluded that the education stakeholders‟ held perceptions and attitudes could either have positive or adverse effects on the affected girls‟ learning outcomes.